2020
DOI: 10.1007/s11356-020-11082-7
|View full text |Cite
|
Sign up to set email alerts
|

Buckwheat, rooibos, and vitex extracts can mitigate adverse effects of xylene on ovarian cells in vitro

Abstract: This study examines whether selected functional food and medicinal plants can mitigate the adverse effects of xylene on ovarian cells. The influences of xylene (0, 10, 100, or 1000 ng/mL), buckwheat (Fagopyrum esculentum), rooibos (Aspalathus linearis), vitex (Vitex agnus-castus), extracts (10 μg/mL each), and a combination of xylene with these plant additives on cultured porcine ovarian granulosa cells are compared. Cell viability, proliferation (PCNA accumulation), apoptosis (accumulation of bax), and releas… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
32
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6
1

Relationship

2
5

Authors

Journals

citations
Cited by 11 publications
(34 citation statements)
references
References 36 publications
(48 reference statements)
2
32
0
Order By: Relevance
“…Women exposed to aromatic hydrocarbons (e.g., xylene) had reduced levels of luteinizing hormone (LH) [ 6 , 7 ], follicle-stimulating hormone (FSH), and prostaglandin [ 6 ], as well as pregnanediol 3-glucuronide (pd3G) and estrone 3-glucuronide (E13G) [ 7 ]. In vitro studies showed that xylene was able to affect proliferation, apoptosis, and the release of steroids, peptide hormones, and prostaglandins by cultured murine [ 8 ], porcine [ 9 , 10 , 11 ], and bovine [ 12 ] ovarian cells. The adverse effects on the ovary could be due to the ability of xylene to induce oxidative stress and to affect the production and reception of steroid hormones, as well as the intracellular regulators of ovarian cell proliferation and apoptosis [ 2 ].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Women exposed to aromatic hydrocarbons (e.g., xylene) had reduced levels of luteinizing hormone (LH) [ 6 , 7 ], follicle-stimulating hormone (FSH), and prostaglandin [ 6 ], as well as pregnanediol 3-glucuronide (pd3G) and estrone 3-glucuronide (E13G) [ 7 ]. In vitro studies showed that xylene was able to affect proliferation, apoptosis, and the release of steroids, peptide hormones, and prostaglandins by cultured murine [ 8 ], porcine [ 9 , 10 , 11 ], and bovine [ 12 ] ovarian cells. The adverse effects on the ovary could be due to the ability of xylene to induce oxidative stress and to affect the production and reception of steroid hormones, as well as the intracellular regulators of ovarian cell proliferation and apoptosis [ 2 ].…”
Section: Introductionmentioning
confidence: 99%
“…One such remedy could be the use of functional food—plant products containing flavonoids, which can act as natural adaptogens, antioxidants, and phytoestrogens [ 2 ]. Previously, the abilities of some plants (buckwheat, rooibos, Vitex Agnus cactus [ 11 ]; Tribulus Terrestris [ 12 ]) and plant molecules (quercetin [ 9 ]) to mitigate xylene effects on cultured porcine and bovine ovarian cells have been reported. Nevertheless, the effects of these plant additives have been studied only in the in vitro systems, but these additives were able to prevent only part of the xylene effect.…”
Section: Introductionmentioning
confidence: 99%
“…Using the cultured porcine ovarian granulosa cells, Sirotkin et al [ 19 ] found that xylene stimulated the build-up of proliferating cell nuclear antigen (PCNA), an indication of increased cellular replication. The result was found to be contrary in their later study, where xylene reduced the PCNA expression [ 21 ]. A xylene compound also surged the apoptotic activity, as shown by an elevated apoptotic marker, Bax, thus reducing the cellular viability.…”
Section: Resultsmentioning
confidence: 66%
“…In vitro studies explored further the protective effects of certain vegetables and medicinal plants against xylene toxicity using bovine and porcine ovarian granulosa cells [ 17 , 18 , 21 ]. Nevertheless, the mechanism of xylene toxicity when absorbed into human and animal bodies is not well understood.…”
Section: Discussionmentioning
confidence: 99%
“…Subsequent studies, however, did not confirm the ability of rooibos additions at dose 10 µg/mL to affect this marker of apoptosis. Furthermore, in these studies rooibos additions promoted accumulation of PCNA, which however did not alter cell viability (Sirotkin, Macejková, Tarko, Fabova, Alrezaki, et al, 2020; Sirotkin, Macejková, Tarko, Fabova, Alwasel, et al, 2020). Furthermore, in these studies rooibos was able to either promote (Sirotkin, Macejková, Tarko, Fabova, Alrezaki, et al, 2020) or reduce (Sirotkin, Macejková, Tarko, Fabova, Alwasel, et al, 2020) progesterone release.…”
Section: Effects On Female Reproductive Processesmentioning
confidence: 77%